2020
DOI: 10.3390/su12197856
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Determinants on Innovations in Small KIBS Firms in the Czech Republic before COVID-19

Abstract: There is still a lack of empirical evidence prevalent about innovation in knowledge-intensive business services (KIBS), and more particular, about determinants of innovations in small firms to sustain their future development. Studies in this area suggest that different determinants will affect different forms of innovation outputs of KIBS. This paper investigates the direction and the significance of these influences on propensity to innovate. The empirical evidence is based on quantitative and firm-level dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, research has often examined large or medium companies, while small KIBS (although they represent the predominant part of this sector) have rarely been investigated (Bumberová & Milichovský, 2020). This article contributes to filling this research gap by exploring and categorizing small and micro KIBS firms, based on their attitude towards KM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research has often examined large or medium companies, while small KIBS (although they represent the predominant part of this sector) have rarely been investigated (Bumberová & Milichovský, 2020). This article contributes to filling this research gap by exploring and categorizing small and micro KIBS firms, based on their attitude towards KM.…”
Section: Introductionmentioning
confidence: 99%
“…First, they generally assume that this is a homogeneous sector or, at most, divided into generic classes based on their particular kind of economic production (as is done in the NACE‐based classifications), or on general structural features (see, e.g., Ciriaci & Palma, 2016; Huggins, 2011). Furthermore, research has often examined large or medium companies, while small KIBS (although they represent the predominant part of this sector) have rarely been investigated (Bumberová & Milichovský, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They found that human resource development and training increase labor productivity twice as much as they increase wages, while later on, they supported only the effects of company training on labor productivity (indirect effect on investment on company equipment). Returns on investments are determined by a company's ability to combine capabilities such as financing, recruiting and training of highly skilled employees, understanding of market needs, and other factors, such as organizational changes (D'Este et al 2012;Bumberová and Milichovský 2020;Corrocher et al 2009).…”
Section: Measurement Of Human Resources Investmentmentioning
confidence: 99%
“…However, human resources management practices, such as training and remuneration management processes, adjusted to create new ideas, may encourage workers to innovate (Fu et al, 2015;Mazzei et al, 2016). Specifically, in KIBS, the structural MI increases when perceived adverse conditions regarding the access to skilled employees to develop SI (Bumberov a and Milichovskỳ, 2020). Firms can develop systematic coding and routing systems for the new service ideas by adapting the different organisational SI development structures (Chung and Tseng, 2019).…”
Section: 3mentioning
confidence: 99%
“…In services organisations, in a strategic combinative adoption of innovation types, the technological process innovations are associated with information TEC (Damanpour et al , 2009), which represents strategic leverage for innovating and differentiating from competitors (Chen et al , 2020; Tomo et al , 2020; Ribeiro-Navarrete et al , 2021). In addition, in KIBS, although TEC has been considered a critical factor in innovation efforts (Miles et al , 1995; Ribeiro-Navarrete et al , 2021), a considerable body of research still emphasises process innovation (Amara et al , 2016; Karlsson and Tavassoli, 2016; Bumberová and Milichovskỳ, 2020). This study seeks to expand the previous innovation research by including TEC use.…”
Section: Literature Review Hypothesis Development and Research Frameworkmentioning
confidence: 99%